Reverse Flow Reactor for Catalytic Oxidation of Lean Methane - Kurniawan, Teguh; Budhi, Yogi Wibisono; Bindar, Yazid (World Chemical Engineering Journal, 2018)
Methane as a potential green house gases contributor which gives 21 GWP has to be mitigated to diminish the global warming effect. High concentration methane can be easily converted into CO2 by mean oxidation. However lean methane can only be oxidized in catalytic reaction system as the catalyst lowers the reaction temperature up to 400 oC. Nevertheless, this is still high temperature to achieve by low concentration and low temperature feed. It still needs preheating the feed until its reaction condition reached which can be supplied outside or within the system called auto thermal. One of promising auto thermal reactor is reverse flow reactor which is the reactor that its feed flow periodically switches to make the heat trapped inside the reactor. In this work we have designed reverse flow reactor by one-dimensional model, pseudohomogeneous for mass and heterogeneous for energy to burn lean methane from a station compressor. The critical parameter of switching time on the system of periodical reversal is also presented